2012
DOI: 10.3892/ijmm.2012.1086
|View full text |Cite
|
Sign up to set email alerts
|

Solid lipid nanoparticles of paclitaxel strengthened by hydroxypropyl-β-cyclodextrin as an oral delivery system

Abstract: The objective of this study was to evaluate the potential of surface-modified paclitaxel (PTX)-incorporated solid lipid nanoparticles with hydroxypropyl-β-cyclodextrin (smPSH). The smPSH released 89.70 ± 3.99% of its entrapped PTX within 24 h when placed in dissolution medium containing sodium lauryl sulfate. The cellular uptake of PTX from smPSH in Caco-2 cells was 5.3-fold increased compared to a PTX solution based on a Taxol formulation. Moreover, smPSH showed an increased cytotoxicity compared to PTX solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Therefore, the small PSC particle size might improve the rate and amount of cellular uptake. 19 Because NSC was prepared using the same method as that of PSC, the high fluorescence observed for NSC is consistent with the results obtained previously.…”
Section: Cellular Uptake Studysupporting
confidence: 88%
See 3 more Smart Citations
“…Therefore, the small PSC particle size might improve the rate and amount of cellular uptake. 19 Because NSC was prepared using the same method as that of PSC, the high fluorescence observed for NSC is consistent with the results obtained previously.…”
Section: Cellular Uptake Studysupporting
confidence: 88%
“…As a reference, the viability of Caco-2 cells treated with PTX solution for 72 hours was 71.45. 19 The inhibition efficiency of PS and PSC containing 5 µM and 10 µM PTX increased upon increasing the incubation time from 24 hours to 48 hours. The cell viability after treatment with PSC significantly decreased upon increasing the incubation time up to 72 hours at both PTX concentrations.…”
Section: Cell Proliferation Studymentioning
confidence: 95%
See 2 more Smart Citations
“…However, various reports have indicated that Cremophor EL may induce a number of serious side effects, including acute neurotoxicity, hypersensitivity, cardio toxicity and nephrotoxicity (11). Recently, an albumin-bound PTX nanoparticle (Abraxane™) became the first Cremophor EL-free PTX agent approved for the treatment of various types of cancer, including lung, breast and pancreatic cancer, by the Food and Drug Administration (Silver Spring, MA, USA) (5,9). The application of this agent in cancer treatment may reduce the toxicities associated with PTX-based therapy and increase the loading efficiency of PTX to >85% [1:9 (w/w) PTX and albumin mixture].…”
Section: Introductionmentioning
confidence: 99%